Management of Drug Eruption in Dermatovenereology Ward of Dr. Soetomo General Hospital Surabaya: Retrospective Study - Dyah Ratri Anggarini; Cita Rosita Sigit Prakoeswa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background:  Drug eruption is a skin alteration with or without the involvement of other organ, which appeared after administration of drug at dose used for prevention, diagnosis, or treatment. The mechanism divided into 2 groups, which are type A (can be predicted) and type B (can not be predicted). Purpose:  To evaluate the management of drug eruption in Dermatovenereology Ward at Dr. Soetomo General Hospital Surabaya. Methods: Retrospective study of drug eruption's patients was performed based on medical records within 2009-2011. Basic data, history of allergies, previous medical history, suspected drugs, diagnosis, and previous treatment were recorded. Results: The largest age group is 25-44 years, ratio of women and men is 1.4: 1, most suspected drugs as the cause of the eruption were paracetamol (59), amoxicillin (23), cefadroxil (17). Most common diagnosis was Steven-Johnson syndrome (SJS) as many as 23.4%, the most widely used treatment was steroids, and the average treatment duration was 10 days. Drug patch test (DPT) was conducted to determine the exact cause of drug eruption as the follow up. Conclusion: Drug eruptions can occur in varying degrees, potential to recur, and life-threatening thus appropriate treatment to prevent it is required. Management included given treatment, patient education regarding drug eruption causes, type of eruption, and DPT to determine the cause of drug eruption.Key words: drug eruptions, management, drug patch test (DPT), retrospective study.